The forms of water connection in silicate compounds and building materials/Vandens ryšio formos silikatiniuose junginiuose ir statybinėse medžiagose - Sasnauskas, Kęstutis; Elzbutas, Henrikas; Palubinskaitė, Danutė (Journal of Civil Engineering and Management, 1999)
While altering manufacturing conditions of building materials and the factors influencing the synthesis of nonorganic compounds a few inner processes such as kinetics, crystallisation, polymerisation and crystalline/chemical structure can be directed towards predictable results; thus the principal characteristics of products, ie mechanical, physical, chemical, etc, can be influenced. An essential role is played by water in the chemistry of non-organic materials, including silicate compounds. This role manifests itself in different stages and ways. This paper deals with the structure of water, with emphasis placed on the values of hydrogen connections, associations and dielectric constant e as well as on their influence on hydration, consequently, on the binding and hardening processes. The paper also deals with the analysis and identification of different forms of water connections in compound mobile water, crystalline water, complex water as well as hydroxides. Application possibilities of the infrared absorption, ie spectroscopy, are presented in more detail. Fig 9 shows the dependence of the dielectric constant ϵ on frequency. Fig 10 shows the dependence of the dielectric constant ϵ on temperature in amorphous SiO2 and quartz with different particle sizes mixed with a small amount of water (1, 13…1, 8 %). Possibilities of applying the dielectrometry method for defining characteristics of water and forms of water connection have been confirmed. Article in Lithuanian. First Published Online: 26 Jul 2012